Polyelectrolyte Biomaterial Interactions Provide Nanoparticulate Carrier for Oral Insulin Delivery - Reis, Catarina Pinto (2008)
Nanospheres are being developed for the oral delivery of peptide-based drugs such as insulin. Mucoadhesive, biodegradable, biocompatible, and acid-protective biomaterials are described using a combination of natural polyelectrolytes, with particles formulated through nanoemulsion dispersion followed by triggered in situgel complexation. Biomaterials meeting these criteria include alginate, dextran, chitosan, and albumin in which alginate/dextran forms the core matrix complexed with chitosan and albumin coat. Smaller size and higher albumin-based acid-protective formulation was orally administered to diabetic rats and glucose reduction and physiological response analyzed. Insulin encapsulation efficiency was 90, 82, and 66% for uncoated, chitosan-coated, and albumin-chitosan-coated alginate nanospheres, respectively. The choice of coating polymer seems to influence insulin release profile and to be crucial to prevent peptic digestion. Physiological response following oral delivery showed that insulin albumin-chitosan-coated alginate nanospheres reduced glycemia ~ 72% of basal values. Albumin serves as an important enteric coating providing acid- and protease protection enabling uptake of active drug following oral dosage.